MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN KEMANDIRIAN BELAJAR SISWA MELALUI PEMBELAJARAN BERBASIS MASALAH - khusnul khotimah; Ali Shodikin; Arezqi Tunggal Asmana (INSPIRAMATIKA, 2021)
This research was motivated by the low critical thinking skills and learning independence of students at Nurul Ummah Sukomalot Integrated Middle School. Teachers mostly use the lecture method when learning takes place. Efforts made to overcome these problems are by applying a Problem Based Learning Model. Based on research that has been conducted at SMP Terpadu Nurul Ummah Sukomalo, this study used a test aid to determine the data results from the students' conceptual understanding ability. Based on data analysis, it can be seen that the sig value in the normality test of critical thinking skills is sig> α then H_0 is accepted, where H_0: The sample from the population is normally distributed. In the hypothesis test, the pretest T_Hitung obtained 37.137, with 20 degrees of freedom, then the posttest T_Hitung obtained 134.240, with 20 degrees of freedom.Based on the determination of the conclusion, that is if T_Tabel <T_Hitung <T_Tabel, where T_Tabel is obtained from the t distribution list with α = 0.05 then H_0 is accepted and H_1 is rejected, so that from the t-test results there are differences in critical thinking skills before treatment and after treatment. Furthermore, in the N Gain test phase, the n gain value obtained was 0.621221424 with the criteria seen from the criteria table 0.3≤g≤0.7 showing the value of n gain for the critical thinking ability in the moderate category. The sig value on the normality test of learning independence is siper> α then H_0 is accepted, where H_0: The sample from the population is normally distributed. Whereas in the hypothesis test, the pretest T_Hitung obtained 20.452, with 20 degrees of freedom, then the posttest T_Hitung obtained 28.407, with 20 degrees of freedom. So that from the t-test results there are differences in student learning independence before treatment and after treatment. The results of the N Gain test on learning independence obtained 0.360068307 where the gain value is less ≤ 0.7 where 0.3≤g≤0.7 with the moderate category